The Organizational Dilemmas of Ethnic Churches: A Case Study of Japanese Buddhism in Canada - Mullins, Mark R. (Sociological analysis, 1988)
Ethnic churches in the course of their development encounter a number of organizational dilemmas. These are related primarily to the tension between the old world language and culture of the first generation immigrants, and that of the adopted host society. The transformation of the ethnic group through the process of assimilation generates these critical internal problems. The purpose of this paper is to analyze this “tension” and its attendant organizational problems as they exist in the Buddhist Churches of Canada, the largest foreign-oriented minority church within the Japanese Canadian community. The Buddhist Churches of Canada (18 congregations) are organizationally linked to the Mother Temple of Jodo Shinshu (True Pure Land Sect), the Nishi Honganji in Kyoto, Japan. A major focus of this paper is upon the problem of religious leadership in an ethnic religious organization that has a highly assimilated membership, but is dependent upon a religious body in the “old country” for almost all of its leaders.